Measurement of exclusive $γγ→ W^+W^-$ production and search for exclusive Higgs boson production in $pp$ collisions at $\sqrt{s} = 8$ TeV using the ATLAS detector - ATLAS collaboration (2860 authors) (2016)
Searches for exclusively produced W boson pairs in the process pp(γγ)→pW+W-p and an exclusively produced Higgs boson in the process pp(gg)→pHp have been performed using e±μ∓ final states. These measurements use 20.2  fb-1 of pp collisions collected by the ATLAS experiment at a center-of-mass energy s=8  TeV at the LHC. Exclusive production of W+W- consistent with the Standard Model prediction is found with 3.0σ significance. The exclusive W+W- production cross section is determined to be σ(γγ→W+W-→e±μ∓X)=6.9±2.2(stat)±1.4(sys)  fb, in agreement with the Standard Model prediction. Limits on anomalous quartic gauge couplings are set at 95% confidence level as -1.7×10-6<a0W/Λ2<1.7×10-6  GeV-2 and -6.4×10-6<aCW/Λ2<6.3×10-6  GeV-2. A 95% confidence-level upper limit on the total production cross section for an exclusive Higgs boson is set to 1.2 pb.